templo de trabalho e fé: estudo sobre mercado informal e ética protestante no shopping centro terceirão em joão pessoa-pb - Silva, Gilvando Estevam da (2010)
Growth in the informal economy is a troubling trend that is beginning to cause a split social consequence, the gradual demoralization of the tax collection system of the State, which formally begins with a minimum of legal norms the development of this economy, with construction space intended for that market. The Shopping Center Terceirão in João Pessoa-PB, is one of those buildings, which highlights the presence of some of these evangelical churches actively participating in business activities and through its symbolic power, direct marketers adherents of a particular sect to use a particular language that identify and heat sales. To understand the scale of representations and the reasons for those actions as well as their interaction with certain subjective signs, semiotic elements were used to compare with Weberian studies, taking into account the spread of Protestantism site, combined with the mercantile spirit, which comes to a "particular ethos" to the interaction of a capitalist conception / informal, with a religious ethics / mercantilist. The study was based on an ethnographic research whose overall objective was to analyze from the transdisciplinarity: religion, morality and economics, the behavior of this triad in the face of an ethical nature of Calvinist religious employed by those churches. As data collection instruments were used participant observation and semi-structured interviews. The results showed that the adoption of ethics that binds a particular religious doctrine with a need, is characterized by the imperative to rationalize the feelings that governs the social and personal relationships of the group and acts as a legitimate element of these churches, therefore, the interaction the dynamics of the informal market with religious agents there is a dichotomous relationship between ideas an interests of the group